Pengenalan Presensi Kehadiran Menggunakan Kode Qr Berbasis Gawai Android - Deden Rosid Waltam; Wawan Budiarto (Institut Teknologi dan Bisnis Semarang, 2024)
Presence recognition training using QR codes based on Android devices could be one of the trainings that can be developed by students because the competency gain from this training is quite promising. If students/santri after becoming alumni can later develop these competencies, it can be very profitable. If in the Islamic boarding school environment the alumni spread across their regions and try in various fields, of course knowledge of using the QR code scanner digital application on Android devices will be very useful, especially for the administration system. Partners in this PKM activity are teachers/administrative staff/students of Assaadah Puri Serpong Islamic High School within the Assaadah Puri Serpong Islamic Boarding School environment. The training on introducing attendance using QR codes based on Android devices was carried out with the stages of introduction, counseling and assistance in the practice of using it. Based on the results of observations and discussions with partners, there are several problems faced, especially related to the student attendance review system which still uses a manual/paper-based system, resulting in difficulties in organizing, processing and controlling student attendance data both at the teaching staff level and in the school administration. The lack of technical knowledge regarding the use of digital applications on Android devices, such as a QR code scanner application which can actually be used for student attendance applications, is one of the obstacles for school equipment to be able to manage a more efficient attendance administration system. The solutions carried out in this PKM activity related to existing problems are: 1. Technical aspect: this aspect includes things you need to know about a simple presence attendance application using a QR code based on an Android device. The PKM team helps with the above matters through counseling and training so that a good understanding of this aspect is obtained so that they are technically able to practice it. 2. Management Aspect: this aspect is related to the management of the presence data obtained. So far, data management is still carried out manually without the use of a good application system. For this reason, the PKM team helps to solve problems in the management aspect with training methods on how to manage student attendance percentage data that is more practical, accurate, effective and efficient.